IDIOSINKRETIVITY OF ADATRECHT ON THE FORMAT DEMOCRACY IN INDONESIA - Bramantyo, Rizki Yudha; Widyati, Satriyani Cahyo; Wahyuni, Niniek; Pudjiono, Bambang (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2020)
The relationship between customary law and national law in the context of developing national law is a functional relationship, meaning that customary law is the main source in obtaining materials needed for the development of national law. Customary law that is needed in the era of globalization or modern times is customary law that is adapted to the conditions and developments of the times, so that customary law shows a dynamic nature so that it can easily develop according to the times because it has universal values and legal institutions. Which is in the form of a modern statement. With this adjustment, it is possible that the purity of the application of the rules of customary law to become national law will experience a shift, as long as it is to enrich and develop national law, as long as it does not conflict with Pancasila and the 1945 Constitution.Keywords: Customary Law; National Law Development; Globalization.